Symbolic Politics of Karaeng Power in Jeneponto - Syarifuddin,; Jumadi,; Muhammad Syukur, (Technium Social Sciences Journal, 2024)
This study explores the symbolic political phenomenon of Karaeng power in Jeneponto, South Sulawesi, Indonesia. The main objective of this research is to understand how Karaeng traditional symbols of power are maintained and utilized in the local political context. Qualitative research methods are used by conducting in depth interviews with community figures and content analysis of related primary and secondary data. The research results show that traditional Karaeng symbols of power still have strong relevance in influencing local political dynamics, even in the modern era and ongoing democratization. The discussion in this paper highlights the importance of understanding the role of symbols in the local political context, as well as its implications for power dynamics and community political participation in Jeneponto.